A blocking flow shop deteriorating scheduling problem via a hybrid chemical reaction optimization. (June 2017) - Fu, Yaping; Wang, Zhanzhong; Zhang, Jihui; Wang, Zhenling
This study presents a blocking flow shop deteriorating scheduling problem which has a widespread application in manufacturing and service systems. In the investigated problem, there is no buffer between machines, and the actual processing time of jobs on each machine is described as a linear function of their starting time and normal processing time. In order to deal with this problem more efficiently, this study develops a hybrid chemical reaction optimization algorithm, where some special strategies are developed based on the problem characteristics, for example, solution representation, on-wall ineffective collision, decomposition, inter-molecule ineffective collision, and synthesis reactions. In addition, a variable neighborhood search is designed to strengthen the search ability of the chemical reaction optimization algorithm. Computational simulation experiments on a set of instances and performance comparisons are provided. They show that the proposed algorithm is superior to the standard chemical reaction optimization and genetic algorithm, which demonstrates that the proposed algorithm is a promising optimizer for the investigated problem.